Mangás: potencialidades e possibilidades para o ensino de Geografia no ensino fundamental - Coelho, Vagner Limiro (2014)
The present research starts from the aim of analyzing the potential of the manga to the geography teaching. This intention is based on the perception that the comics, including manga, have been propagating in the reading of the young Brazilian audience, especially elementary school students. These young people attend school and interrelate in that place of education and socialization where the diversity of cultural elements and meaning production propose the construction of their identity characteristics, often influenced by the consumer industry. Thus, the manga as global media artefacts are gaining ground among the young people and their narratives show themselves in everyday school life, which leads us to investigate such audience, as well as their interpretations and reflections about the manga from a perspective to the teaching of Geography. So, we use different instruments to collect data, as the application of semi-enclosed questionnaires and the realization of focal groups, in order to analyze the notions / geographical comprehensions of these young students, through the reading and interpretation of the manga Naruto and Naruto Shippuden. As a result, we realized that the artifact by itself presents difficulties to adding basic knowledge of geography, since this does not specifically pedagogical or didactic intentions. However, he seduces as it is systematically assimilated by young people and, with a coherent intermediation by the teachers and changes in the school attitudes, may submit elements - in its origin, format and narrative - that could contribute to un effective teaching of Geography.